Ethics of Reproductive Education for Children According to the Book of Tarbiyat al-Aulad fi al-Islam by Abdullah Nashih ‘Ulwan - Nurjanah, Nunung; Tantowie, Tanto Aljauharie (Graduate Program, Darussalam Institut for Islamic Studies, 2018)
One of the problems of child education that is very serious in the environment of Islamic education institutions is about sexual education. There are views that are pro and contra to the implementation of sexual education in Islamic education institutions. However, as long as sexual education is carried out based on ethical norms, sexual education remains important for children. This study succeeded in exploring a number of ethics that can be used as the basis for the implementation of sexual education for children.